Blood Pressure and Prevention of Stroke - Dakay, Katarina; Silver, Brian (Seminars in Neurology, 2017)
Stroke is a common cause of morbidity and mortality worldwide, and hypertension is the most common modifiable risk factor for stroke. The treatment of hypertension reduces the primary occurrence of stroke as well as the risk of stroke recurrence. Although there are conflicting data regarding the optimal blood pressure for stroke prevention, an individualized approach taking into account the patient's age, comorbidities, and side effects of medication is a helpful strategy. Current guidelines support the pursuit of a systolic blood pressure under 140 mm Hg for both primary and secondary stroke prevention, though recent data suggest a more intensive goal may be of benefit in select patients. Certain classes of antihypertensives may be more beneficial in stroke prevention than others. Trials are underway to further study the optimal blood pressure target for stroke prevention in specific populations as well as the potential benefits of intensive blood pressure reduction beyond the current guidelines.
Keywords: hypertension; blood pressure; prevention; stroke